Infrared spectroscopy: a tool for determination of the degree of conversion in dental composites - Luciene Gonçalves Palmeira Moraes; Renata Sanches Ferreira Rocha; Lívia Maluf Menegazzo; Eudes Borges de Araújo; Keizo Yukimito; João Carlos Silos Moraes (University of São Paulo, 2008)
Infrared spectroscopy is one of the most widely used techniques for measurement of conversion degree in dental composites. However, to obtain good quality spectra and quantitative analysis from spectral data, appropriate expertise and knowledge of the technique are mandatory. This paper presents important details to use infrared spectroscopy for determination of the conversion degree.